Current principles of effective therapy for ovarian cancer - L. A. Ashrafyan; V. I. Kiselev; E. L. Muizhnek; E. V. Gerfanova; I. B. Antonova; I. N. Kuznetsov; O. I. Aleshikova (ABV-press, 2015)
In spite of all of modern medicine»s advances, ovarian cancer (OC) mortality remains to be incommensurably high and to hold the lead among gynecological cancers. The initial cause of this deplorable statistics is the absence of a clear concept of the pathogenesis of OC and hence the justified prevention and methodology of early diagnosis of the disease; in this connection, therapy that proves to be ineffective is frequently used by medical oncologists in their daily practice. As a consequence, there is a high proportion of its further progression: the rates of early and late recurrences were about 30 and 60-65 %, respectively; most of which are drug resistant to further chemotherapy cycles. By taking into account these strikingly modest statistics, it becomes apparent that oncologists desire to make changes in the existing treatment regimen to achieve meaningful results. To use target drugs is one of these promising areas owing to new views on the concept of the pathogenesis of OC.Nevertheless, considering a wide variety of the signaling cascades and molecules, which are involved in the process of carcinogenesis, even target compounds, if they have only one point of application, cannot always produce their desirable therapeutic effect and their co-administration is responsible for high toxicity. In this light, the most effective drugs are indole-3-carbinol and epigallocathechin-3-gallate, which virtually cause no adverse reactions and can block various molecular targets at different levels of the mechanism of malignant transformation. Based on L. A. Ashrafyan, s concept of two pathogenetic variants of sporadic OC (2009) and on the recent findings in molecular biology and epigenetics, the incorporation of the above medications into the standard treatment regimen for OC should increase survival rates and change the nature of recurrence by that of more locally advanced forms. On this basis, a clinical trial was carried out to study the efficiency of using antitumor drugs based on indole-3-carbinol and epigallocathechin-3-gallate as part of combination therapy for OC. The results of the clinical trial performed are suggestive of considerably higher survival rates in the groups receiving the above drugs than in the control groups. In addition, the multitarget effect of indole-3-carbinol and epigallocathechin-3-gallate can effectively remodel the function of a cancer stem cell, the main source of recurrences and metastases, and may be considered as an important adjunct to the existing strategy of antitumor therapy.